The Development Practicum Based e-Module Local Wisdom the Chemistry Subject of Acids and Bases - Wahyu Fatihah; H. M. Syadeli Hanafi; Lukman Nulhakim (Pendidikan Kimia Unimus, 2023)
The subject matter of acids and bases in the chemistry learning syllabus for class XI IPA is KD 3.10 and KD 4.10. In reality, many teachers do not carry out KD 4.10 activities for various reasons, especially the limited tools, and materials in the laboratory. This study aims to create a practicum e-module based on local wisdom in acid-base chemistry subject. Most of the tools and materials used were obtained from the surrounding environment. The research method used was a qualitative description, namely analyzing several sources of literature and the results of practicum e-modules that have been prepared before being applied in learning activities. This study resulted in an interactive practicum e-module and fulfilled the criteria set by the Ministry of Education and Culture in 2003 regarding guidelines for writing good modules. In general, the resulting e-modules are divided into learning activities in theory to recall the learning material that has been carried out to support practicum activities and practicum activities which are the main activities of creating the e-module. In conclusion, the use of tools and materials in the form of local wisdom for practicum activities in acid-base courses can increase students' insight that learning chemistry practices are not always expensive and use hazardous chemicals.